Quiet eye training in sports - Wilson, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Recent research has demonstrated that quiet eye (QE) training interventions provide a performance advantage over traditional, technique focused interventions. Following early work by Vickers and colleagues (e.g., Adolphe et al., 1997; Harle & Vickers, 2001), recent research by Causer and colleagues in shotgun shooting (Causer et al., 2010, 2011) and our own team in basketball (Vine & Wilson, 2011), football (Wood & Wilson, 2011, 2012) and golf (Moore et al., 2012; Vine & Wilson, 2010; Vine et al., 2011) has supported the efficacy of such training. The premise of these training interventions is that if a performer can optimise the information they receive from their eyes, they can optimise movement (without having to explicitly focus on the control of movement). The research has followed three main lines of enquiry: (1) Training expert performers to fine-tune skills, (2) training novices to acquire new skills, and (3) in both cases, trying to determine if the learning is more resilient to pressure. Consistent findings show that quiet eye training is more effective than traditional scripts focusing on movement control across all three areas. What has been less well understood is why such training is beneficial. The current talk will focus on potential visuomotor, attentional and psychological control explanations as explored in our most recent studies. Furthermore, the implications of applying quiet eye training outside of sport to other performance domains (including, surgical technical skills, military marksmanship, and children with coordination difficulties) will also be discussed.